Effect of T2DM progressing on renal glucose excretion till the TmG - محمود سليمان شاكر; احمد محمد الجلبي لؤي (Tikrit Journal of Pharmaceutical Sciences, 2023)
In this study, an attempt has been made to measure the amount of glucose excreted in urine regarding the duration of T2DM. In order to achieve that 302 T2DM patients have been included and then classified into 3 groups according to duration of illness.T2DM patients have been tested for random blood glucose, urine glucose concentration and serum creatinine while glomerular filtration rate (GFR), tubular glucose load (TGL) and urine glucose excretion (UGE) have been calculated. Then an analytical tests were applied to analysis these parameters and comparing the results of different groups according to classification of this study. The maximum transport of glucose (TmG) , and UGE till the TmG (splay region) are varied between T2DM patients. In order to evaluate the validity, ANOVA test for groups variance, and linear regression were applied. According to this study the TmG increased and the UGE till the TmG decreased as the duration of illness increased